2019
DOI: 10.3390/pharmaceutics11070350
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Aceclofenac Proniosomes by Using Different Carriers, Part 1: Development and Characterization

Abstract: In the contemporary medical model world, the proniosomal system has been serving as a new drug delivery system that is considered to significantly enhance the bioavailability of drugs with low water solubility. The application of this system can improve the bioavailability of aceclofenac that is used for the relief of pain and inflammation in osteoarthritis, rheumatoid arthritis, and ankylosing spondylitis. The present study is intended to develop an optimized proniosomal aceclofenac formula by the use of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Therefore, 5 min hydration time is selected for further studies because short hydration time would improve patient acceptability and product applicability. Other researchers such as Sammour et al [34] reported that the hydration time has a significant (p < 0.05) negative effect on %EE. However, Ruckmani and Sankar found that more drug would be entrapped within the vesicles at longer hydration time [51].…”
Section: Preliminary Screening Studiesmentioning
confidence: 84%
See 3 more Smart Citations
“…Therefore, 5 min hydration time is selected for further studies because short hydration time would improve patient acceptability and product applicability. Other researchers such as Sammour et al [34] reported that the hydration time has a significant (p < 0.05) negative effect on %EE. However, Ruckmani and Sankar found that more drug would be entrapped within the vesicles at longer hydration time [51].…”
Section: Preliminary Screening Studiesmentioning
confidence: 84%
“…The results investigated that the volume of the hydration had a significant negative impact (p < 0.05) on EE%. These findings could be attributable to increased leakage of the drug from niosomal vesicles at larger hydration volume [34]. However, the time of hydration had no significant effect (p > 0.05) on %EE.…”
Section: Preliminary Screening Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…This suggested possibility of ACV turned into the disordered crystalline state due to the molecular interaction with lecithin and chitosan. By comparing ACV and PALN1 diffractogram, a broad peak emerged with sharp peak diminishment indicating ACV entrapped in LPNPs system in the amorphous state of the nanoparticles ( 41 ).…”
Section: Resultsmentioning
confidence: 99%